(untitled) (LACCEI, 2024)
The objective of the document is to determine the effects of the Covid-19 pandemic on the economic returns of education in Peru for the year 2021, for this purpose we compare the marginal effects obtained by each educational level achieved with the results of the year 2019, this contrast is made after estimating the relationship known as the Mincer equation by the method of ordinary least squares, working in the first instance with all the information, then complementing the analysis with regressions by quantiles that provide us with a response conditioned to the levels from income. Likewise, we include control variables that expand our study since it adds characteristics of the individuals, their employment status and geographic location.